(Invited) Recent Advances in Porous Silicon Based Microelectronic Devices. (20th July 2018) - Gautier, Gael; Billoué, Jérôme; Defforge, Thomas; Lu, Bin; Bardet, Benjamin; Lascaud, Julie; Menard, Samuel
Abstract : In this paper, we show some recent advances that have been performed in the field of Porous Silicon (PSi) applied to microelectronic devices. Indeed, many components can implement the specific properties of this nanostructured material. Therefore, it has been identified as a serious candidate for the integration of complex functions in a single silicon wafer in a "more than Moore" context. In particular, it will be shown that PSi etching is nowadays mastered at a wafer scale on localized areas, 3D surfaces or on the backside of devices. Some typical examples of applications such as RF devices, AC power switches or ultrasonic transducers will be described in order to illustrate the benefits PSi technology can provide.